Language of the legal process: an analysis of interactions in the Syariah court - Hashim, A. (De Gruyter, 2011)
This study examines interactions from trials in the Syariah court in Malaysia. It focuses on the types of questioning, the choice of language and the linguistic resources employed in this particular context. In the discourse of law, questioning has been a prominent concern particularly in cross-examination and can be considered one of the key communicative practices in legal encounters. Usually based on expectations and assumptions about what the responses are likely to be, an extended question and answer dialogue can allocate or remove blame and make a party appear trustworthy or unreliable. Questions which are supportive of witnesses can simply ask for confirmation, leading witnesses through straightforward narratives and information-seeking questions. On the other hand, questions during cross-examination create a negative evaluation of witnesses and defendants, destroying their credibility and casting doubts on defence statements. Data are collected from a Syariah court in the country and examined for the strategic lexical choices, specific linguistic resources, including code-switching, through which utterances are constructed as questions and how questions are sequenced in this particular context.